Ensemble Analysis Identifies Nasal 15-Keto-PGE2 as a Predictor of Recovery in Experimental Rhinovirus Colds. (3rd March 2021) - Lane Starr, Nicole M; Evans, Michael D; Lee, Kristine E; Gern, James E; Denlinger, Loren C
Abstract: Background: Symptom intensity during a common cold is highly variable, particularly after the illness peaks, contributing to delay in recovery. Rhinoviruses frequently cause colds and, during acute infections, generate leukotriene B4 and prostaglandin E2 (PGE2 ). PGE2 is known to initiate oxylipin class switching and resolution of acute inflammation. Thus, we hypothesized that during acute rhinovirus colds, oxylipins with pro-resolving capabilities reduce symptom severity and speed recovery. Methods: Four groups of healthy volunteers were inoculated with placebo or 3 different doses of rhinovirus A16. Participants kept daily records of symptoms and contributed serial nasal lavage fluid samples. We collected semi-quantitative mass spectrometry data for 71 oxylipins in these acute samples from all participants. An ensemble analysis approach was used to further reduce this dataset. Results: Levels of 15-keto-PGE2 at day 3 of the cold were consistently among the top candidates in these models of recovery symptoms. 15-keto-PGE2 was the only oxylipin with an interaction between inoculum dose and time. Acute 15-keto-PGE2 levels were inversely associated with symptoms during cold recovery in a multivariable analysis ( P = .0043). Conclusions: These findings show that high 15-keto-PGE2 levels during the acute cold are associated with fewer symptoms during recovery. Abstract : A novel data reduction strategy identifies the oxylipin 15-keto-PGE2 as an important mediator in recovery following an experimental rhinovirus infection in humans. High levels of this oxylipin were associated with a faster recovery and fewer symptoms.